A Comparative Study of Densification of Sol‐Gel‐Derived Nano‐Mullite due to the Influence of Iron, Nickel and Copper Ions. Issue 6 (15th May 2013) - Roy, Debasis; Bagchi, Biswajoy; Bhattacharya, Alakananda; Das, Sukhen; Nandy, Papiya
<x xml:space="preserve">Abstract</x> By sol‐gel process, mullite samples doped with 0.002M, 0.02M, 0.1M, 0.15M, and 0.2M of iron, nickel, and copper are prepared. Prepared gels were then dried, grinded, pressed into pellets, and sintered at temperatures 1000°C and 1300°C for 4 h. Mullite densification behavior was analyzed. Our intention is to study the role of metal ions in influencing mullitization behavior in the case of the sol‐gel reaction process, to provide useful information of mullite. This study deals with the effect of metal ions on mullite formation, microstructure, and densification behavior in single‐phase sol‐gel‐derived mullite.